2015
DOI: 10.1155/2015/249098
|View full text |Cite
|
Sign up to set email alerts
|

Improvement ofIn VitroOsteogenic Potential through Differentiation of Induced Pluripotent Stem Cells from Human Exfoliated Dental Tissue towards Mesenchymal-Like Stem Cells

Abstract: Constraints for the application of MSCs for bone reconstruction include restricted self-renewal and limited cell amounts. iPSC technology presents advantages over MSCs, providing homogeneous cellular populations with prolonged self-renewal and higher plasticity. However, it is unknown if the osteogenic potential of iPSCs differs from that of MSCs and if it depends on the iPSCs originating cellular source. Here, we compared the in vitro osteogenesis between stem cells from human deciduous teeth (SHED) and MSC-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 35 publications
4
37
0
2
Order By: Relevance
“…Currently, autologous stem cell transplantation [43], a new regenerative treatment in bone tissue engineering techniques, requires promising therapeutic stem cells. SHEDs, compared with BMSCs and DPSCs, possess the properties of being easily obtained, harmless to the human body, having a low risk of immune rejection and cross-infection, and having higher osteogenic and neurogenic differentiation capacity [11,[44][45][46]. Further, they have been recognized as promising stem cells for regenerative medicine.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, autologous stem cell transplantation [43], a new regenerative treatment in bone tissue engineering techniques, requires promising therapeutic stem cells. SHEDs, compared with BMSCs and DPSCs, possess the properties of being easily obtained, harmless to the human body, having a low risk of immune rejection and cross-infection, and having higher osteogenic and neurogenic differentiation capacity [11,[44][45][46]. Further, they have been recognized as promising stem cells for regenerative medicine.…”
Section: Discussionmentioning
confidence: 99%
“…Upon in vivo subcutaneous implantation into immunodeficient mice for 12 weeks, bone constructs engineered using BC1-iPSC-MSCs displayed higher mineral content compared with iPSC-MSCs derived from fibroblasts [50]. Another study reported that iPSCs from human deciduous teeth stem cell (SHED) exhibited significantly higher osteogenic potential than iPSCs from dermal fibroblasts via an in vitro osteogenesis comparison [51]. Hynes et al generated MSC-like cells from iPSC lines arising from three different somatic tissues: gingiva, periodontal ligament (PDL) and lung, respectively [52].…”
Section: Discussionmentioning
confidence: 99%
“…Compared to Other Types of Cells. The osteogenic differentiation ability of iPSCs-MSCs in comparison to MSCs was examined in a variety of studies [86,[93][94][95]. A study on iPSCs showed a delayed expression of osteogenic markers such as COL1A1 and bone sialoprotein (BSP) as well as weaker osteoblastic differentiation and mineral deposition, compared to human BM-MSCs in vitro [57].…”
Section: Osteogenic Differentiation Capability Of Ipscsmentioning
confidence: 99%